A quasi-experimental intervention protocol to characterize the factors that influence the acceptance of new foods by infants: mothers' diet and weaning method. Dastatuz project - Iratxe Urkia-Susin; Diego Rada-Fernandez de Jauregui; Estibaliz Orruño; Edurne Maiz; Olaia Martinez (BMC, 2021)
Abstract Background Children usually refuse to eat and taste fruits and vegetables; and turning unhealthy eating habits around is an important social challenge in industrialized countries. The Dastatuz project aims to study children food neophobia and to enhance fruit and vegetable acceptance. Methods A quasi-experimental, multicentre, controlled and prospective intervention study is proposed, in which early factors influencing new food acceptance will be studied. Mothers in the third trimester of pregnancy (n = 144) and their infants will be the study population. Experimental groups will be established based on mothers´ fruit and vegetable intake (standard or high intake) and weaning method (baby lead weaning vs spoon feeding). The project will assess the possible impact of maternal diet and complementary feeding on infants eating behaviour until 18 months of age. Outcome measures will comprise maternal diet and psychological features during pregnancy and breast-feeding (validated questionnaires). Compositional and physicochemical analysis of milk during breastfeeding will also be carried out. During weaning, until 18 months of age, children's diet will be assessed with 24 h recalls and acceptance of new fruits and vegetables will be studied using video recording. Discussion If the intervention is effective, this research work would have a high potential to be transferred to future public health programs or nutrition guidelines, as a feasible solution to achieve a higher intake of fruits and vegetables among children. Trial registration This study is registered at ClinicalTrials.gov. Identifier: NCT04262102 . Registration date: February 10, 2020 - Retrospectively registered.